Adaptation Strategy of Tidal Flood Handling a Case Study in Sayung Sub-District, Demak - Sarasadi, Annisa; Rudiarto, Iwan; Faradila, Alya (Faculty of Social Science, Universitas Negeri Semarang, 2021)
Sayung subdistrict is one of the sub-districts located on the north coast of Demak Regency which until now experienced rob floods that threaten the social, economic, and physical conditions of the environment. A series of adaptation strategies as a form of mitigation against rob floods are needed to minimize risk. This study aims to analyze the adaptation strategy and implications of tidal flooding on the living systems of coastal communities in Sayung District, including the villages of Sriwulan, Surodadi, Bedono, and Timbulsloko. The research approach used is descriptive quantitative. Data collection is done by sampling method and survey technique using a questionnaire which is then calculated the percentage of each component. So that various community efforts can be seen based on the level of adaptation capacity and structural adaptation.